(untitled) (Environmental Smoke, 2023)
The Central Campus of the Federal University of Paraíba, located in João Pessoa, has 12 forest fragments with approximately 84 ha of Atlantic Forest where a population of Bradypus variegatus Schinz, 1825 inhabites and has been exposed to anthropogenic disturbances. The present study aims to identify, describe and analyze anthropogenic disturbances on the population of B. variegatus that inhabits the atlantic forest fragments on the Central Campus of the Federal University of Paraíba, located in João Pessoa, Paraíba, Northeastern Brazil. Observations were carried out from September 2021 to January 2022 using the ad libitum method through daily 4-hour walks around the fragments. Locomotion behavior was recorded in 16% (n=45) of the 269 observations. An average of 24.5 (n=3 to 61) sloth sightings were recorded per fragment. The correlation between disturbances and the number of recorded sightings was positive and significant, which demonstrates the resilience of B. variegatus in an urbanized environment. Situations classified as low risks prevailed, probably due to the social isolation imposed by the period of COVID-19 pandemic. High risks were 17.5% (n=47) for vehicles, 14.9% (n=40) for domestic animals and 1% (n=3) for people. Results showed that the human activities surrounding the forest fragments cause disturbances in the population of B. variegatus and efforts to mitigate the disturbances caused to these animals must be done, such as forest densification, the accumulation of litter in areas between fragments to avoid falls into the impervious surface and forest connection through rope bridge arboreal overpasses in hotspot areas with a higher density of sloths.